A personal narrative on understanding and navigating transitional change: lessons learned by an accounting academic amidst COVID-19. Issue 2 (11th January 2021) - Ackermann, Christo
Abstract : Purpose: This paper aims to present the personal narrative of an accounting academic, seeking to make sense of his transition change-response to online accounting education, through the thematic lens of the transition cycle of change. Design/methodology/approach: The research approach falls under the umbrella term of autoethnography. An autoethnography is presented as a personal narrative that focused on a specific event in life. Findings: The author found that gaining awareness of how resistance to change manifests itself in the early stages of transition allows us to move forward, rather than remaining "stuck in transition". Furthermore, the author found that transition cycles can be looped; in other words, we find ourselves starting transition anew if circumstances change again. Thus, transition should not be seen as linear but cyclical. Practical implications: This research could be useful to other accounting academics by fostering an awareness of individual change-responses during times of crisis, thereby enabling better self-management of change. For heads of accountancy academic departments, it is important to take note that change amidst crisis can sap morale and diminish work performance. The management of staff, and understanding their transition change-responses during crisis, is therefore critical to ensure that staff are navigated through change arising from crisis. Originality/value: This paper answers the question what can we learn by understanding our transitional process of change by drawing on change theory? To this end, this paper presents and starts this conversation, through a personal narrative bringing to life the transitional change journey of an accounting academic during crisis. This study lays a foundation for further empirical and theoretical enquiry into accounting education change processes during crisis.